Analisis Peranan Perempuan dalam Pembangunan Politik Berwawasan Gender: Studi Dokumentasi Tentang Gender di Indonesia - Lambertha Gundalibra Sari; Mohammad Rozikin Rozikin (Syntax Idea, 2022)
Gender equality and women's representation in Indonesia's political development are crucial issues that have become endless problems for Indonesia. The gap in representation between women and men is seen in the low percentage of women political participants who occupy positions in the DPR RI. The purpose of this study is to examine and analyze the role of women in political development in Indonesia and to determine the factors that influence the low involvement of women in the political sphere. This study uses a qualitative method based on the philosophy of positivism with a documentation study approach that obtains sources of information through texts, manuscripts, and previous research. Based on the results of documentation and literature studies, it is known that women's participation in Indonesia is still quite low even though the government has issued a law that regulates women's representation in political parties. The results show that the problem of the gap in the participation of women and men in political development in Indonesia is caused by the feminine factors inherent in women, in order to overcome this, women need to improve their quality so that they can participate more in political development in Indonesia.